Exact formula for distribution of sequences {ωn} - Shahverdian, Ashot; Kilicman, Adem (World Scientific Publishing, 2013)
An exact formula for distribution of sequences of fractional parts is proved. This provides us with a possibility for computational study of their discrepancies by the means of integer-number programming.